In Centralized Health Systems, Much Is Left Out When Analyses of Local HiAP Strategies Are Limited to Public Administration; Comment on "A Realist Explanatory Case Study Investigating How Common Goals, Leadership, and Committed Staff Facilitate Health in All Policies Implementation in the Municipality of Kuopio, Finland" - Eric Breton; Yann Le Bodo (Kerman University of Medical Sciences, 2023)
We argue that the lessons drawn by Guglielmin and colleagues, from the Health in All Policies (HiAP) approach in the municipality of Kuopio, are of limited use to centralised health systems. There is a need for research more attuned to the circumstances of local governments that have little power over the provision of health programmes; yet can address a range of determinants of population health. In these cases, adopting a state-centric perspective may fail to capture the role of other actors such as non-governmental organizations (NGOs) and local branches of state agencies. Evidence from France shows that centralised health systems can foster HiAP locally through political commitment and dedicated coordination staff whose role is to mobilise and support NGOs, inhabitants, and other local branches of regional and central governments. We highlight, as three important challenges, the issue of legitimacy, funding and positioning of the HiAP instrument in the local government structure.